The Effect of Moringa Leaf Cilok Supply on Hemoglobin Levels of Female Adolescents with Anemia - Dian Soekmawaty Riezqy Ariendha; Sri Handayani; Yopi Suryatim Pratiwi (Universitas Islam Bandung, 2022)
Blood that contains less iron can cause anemia. This nutritional case is the most common in almost all countries, including Indonesia. Female adolescents are more at risk of anemia due to stress, eating late, and losing large amounts of iron during menstruation. One part of the moringa plant (Moringa oleifera), namely the leaves, is believed to increase hemoglobin levels. The method of attracting adolescents to moringa leaf is by processing the moringa leaf becomes a snack called moringa leaf cilok. This research aims to determine the hemoglobin level of adolescent girls who experience anemia before and after being given moringa leaves cilok. This is experimental research with one group pre-post test design from October to November 2021 in Mataram. The subjects in this research are female adolescents with anemia who met the sample criteria. The sample used is n1=n2=32 respondents. The treatment group received moringa leaf cilok and was controlled tablets by giving iron tablets. The data collected was processed by a nonparametric test. The results show an effect of giving moringa leaf cilok on the hemoglobin levels of adolescent girls (p>0.05). The content of iron and vitamin C in moringa leaves cilok has increased hemoglobin levels. This research concludes that moringa leaf cilok can increase hemoglobin levels in female adolescents. Therefore, consuming moringa leaves cilok regularly can be used to treat anemia.